Many-Electron and Multiphoton Atomic Processes: A Tribute to Miron Amusia - Kheifets, Anatoli; Gribakin, Gleb; Ivanov, Vadim (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue contains contributions from colleagues, former students and collaborators of the late Prof. Miron Amusia, who was a world-leading figure in theoretical atomic physics over the past half a century. The focus of this Special Issue is on many-electron and multiphoton atomic processes that are at the forefront of contemporary atomic and molecular physics. Special attention is given to the many-electron correlation problem and its interplay with strong field laser-atom interactions. These scientific advances represent the lasting legacy of Prof. Amusia and his school.